Caring Together: Trajectories of Paid and Family Caregiving Support to Those Living in the Community With Dementia. (16th January 2022) - Reckrey, Jennifer M; Li, Lihua; Zhan, Serena; Wolff, Jennifer; Yee, Cynthia; Ornstein, Katherine A
Abstract: Objectives: Paid caregivers (e.g., home health aides) often work with family caregivers to support persons living with dementia at home. We identify (a) unique trajectories of paid and family caregiving support among persons living with dementia with high care needs and (b) factors associated with these trajectories. Methods: We used group-based multiple trajectory modeling to identify distinct trajectories of paid and family caregiving hours among National Health and Aging Trends Study respondents with dementia who died or moved to a nursing home ( n = 334, mean follow-up 5.5 years). We examined differences between trajectory groups and identified factors associated with group membership using generalized estimating equation modeling. Results: A 3-group model best fit our data: (a) "low/stable care" (61.3% of respondents) with stable, low/no paid care and moderate family care, (b) "increasing paid care" with increasing, moderate paid and family care, and (c) "high family care" with increasing, high family care and stable, low paid care. While both the "increasing paid care" and "high family care" groups were more functionally impaired than the "low/stable care" group, the "high family care" group was also more likely to be non-White and experience multiple medical comorbidities, depression, and social isolation. Discussion: Study findings highlight the importance of considering unique arrangements in dementia care. Receipt of paid care was not only determined by patient care needs. Creating equitable access to paid care may be a particularly important way to support both persons living with dementia and their family caregivers as care needs grow.